Metal-phenolic aldehyde network mediated super-hydrophobic sponge with layered rough surface as well as preparation method and application of metal-phenolic aldehyde network mediated super-hydrophobic sponge
By utilizing the coordination reaction between Fe2+ and TA on the sponge surface, the problem of poor hydrophobicity of TA-Fe3+ coating in the prior art is solved, and the superhydrophobic/super-friendly sponge is achieved Oil characteristics and stability, suitable for oil-water separation applications.
Patent Information
- Application Number
- CN202411759289.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, the surface hydrophobicity mediated by direct assembly or layer-of-layer self-assembly structures are poor, and additional rough structures are required to improve hydrophobicity, resulting in a complicated preparation process.
Fe2+ instead of Fe3+, coordinate with TA through slow oxidation of Fe2+, a rough intermediate layer with a layered spherical structure is constructed in situ on the sponge surface, and a sponge with a superhydrophobic surface is prepared by modification of octamine.
The superhydrophobic/super lipophilic properties of the sponge surface are achieved, the water contact angle can be greater than 165°, and it remains stable in a strong acid, strong alkali and high salt environment, suitable for oil-water separation.
Smart Images

Figure CN119431881A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption separation, and specifically relates to a super-hydrophobic sponge with a layered rough surface mediated by a metal-phenolic network, and a preparation method and application thereof. Background Art
[0002] The continuous growth of global energy demand has stimulated the rapid development of oil-related industries, and also intensified the threat of oil spills and industrial oily wastewater discharge to the ecological environment and human health. In the past, traditional cleaning technologies such as in-situ combustion, flotation, and centrifugation have been widely used in oil-water separation, but these methods often have limitations such as high energy consumption, low separation efficiency, and easy secondary pollution. Therefore, seeking cost-effective oil-water separation technology is an urgent need for water, energy, and environmental security.
[0003] The essence of oil-water separation is an interface problem. With the in-depth study of biological interface wetting theory, porous adsorbent materials with superhydrophobic / superoleophilic (SHB / SOL) properties have attracted widespread attention due to their ability to selectively remove oil components. In particular, for emergency treatment of oil spills in open areas such as lakes or oceans, oil can be collected by simply placing adsorbent materials in the contaminated area. In addition to intermittent adsorption operations, superhydrophobic porous materials can also achieve continuous separation of the oil phase under suction, thereby simplifying oil production operations and reducing costs. Among traditional porous adsorbent materials, commercial polymer sponges such as melamine and polyurethane have the characteristics of low cost, high resilience, high porosity, and large specific surface area, and can be used as candidate materials for oil-water separation. However, unmodified sponges are both hydrophilic and oleophilic, lacking selectivity for oil and water. Therefore, commercial sponges need to be surface modified to give them SHB / SOL properties.
[0004] The key part of biomimetic superhydrophobic surface design is the mutual synergy between the surface micro-nano roughness structure and the low surface energy components. According to the Wenzel and Cassie wetting model, the hierarchical roughness structure is crucial to the construction of superhydrophobic surface. To date, various surface post-treatment methods such as dip coating, plasma treatment, vapor deposition and hydrothermal treatment have been used to adjust the three-dimensional low surface energy roughness structure of sponges. However, most methods are cumbersome and expensive, making it difficult to achieve large-scale industrial applications. More importantly, since the chemical interaction between the surface modifier and the substrate needs to be adjusted according to the specific situation, there are few simple and universal strategies for substrate surface modification.
[0005] In recent years, metal-phenolic networks (MPNs) formed by chelating phenolic materials with metal ions have made substantial progress due to their non-selective adhesion properties and as interlayers, they provide a general platform for further modification by physical or chemical methods. 3+MPNs composed of Fe and tannic acid (TA) have been studied most extensively. The preparation routes of MPNs coatings on substrates can be divided into two categories: direct assembly and multi-step assembly (such as layer-by-layer assembly). In direct assembly, the substrate is coated with TA and Fe. 3+ The coordination reaction is completed in the mixture, and the coordination reaction is quickly terminated within almost 1 minute to form a coating with a thickness of about 10 nm, which means that the deposition of the complex is extremely limited. For the preparation of thicker coatings, the layer-by-layer assembly process is basically the first choice, but the preparation process is cumbersome. It is worth noting that since MPNs themselves are not hydrophobic, the construction of the hydrophobic surface requires the introduction of additional low surface energy molecules. More importantly, for the MPNs-mediated bionic superhydrophobic surface, since the MPNs coating constructed by traditional methods is relatively smooth, additional micro-nanoparticles are usually required to construct a rough hierarchical structure, and then modified with low surface energy molecules, which undoubtedly increases the complexity of the preparation process. For example, Li et al. first prepared the bionic superhydrophobic surface by immersing kapok in TA and Fe 3+ An MPNs layer was formed on its surface in a mixed solution, and then ZIF-8 particles were in situ grown on the MPNs-mediated kapok surface to construct a rough hierarchical structure. Finally, dodecane was introduced to prepare an aerogel with a superhydrophobic surface. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a metal-phenolic network-mediated superhydrophobic sponge with a hierarchical rough surface, using Fe 2+ Replace the traditional Fe 3+ , using Fe 2+ The slow oxidation of TA coordinates with TA, and in situ constructs a rough intermediate layer with a hierarchical spherical structure on the sponge surface to solve the problem of TA-Fe constructed by direct assembly or layer-by-layer self-assembly in the prior art. 3+ The coating-mediated surface hydrophobicity is poor and the technical problem of the need to introduce additional rough structures to improve hydrophobicity.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The first technical purpose of the present invention is to provide a metal-phenolic network-mediated super-hydrophobic sponge with a hierarchical rough surface, using tannic acid TA-Fe 3+ The phenolic hydroxyl groups of tannic acid (TA) molecules in the network reacted with the amino groups in octadecylamine molecules through Michael addition reaction and Schiff base reaction, and the low surface energy molecule octadecylamine was modified on the sponge skeleton to prepare a biomimetic superhydrophobic sponge with a rough hierarchical structure and low surface energy.
[0009] The second technical purpose of the present invention is to provide a method for preparing a super-hydrophobic sponge with a hierarchical rough surface mediated by a metal-phenolic network as described above, which comprises immersing a porous sponge in a mixture of tannic acid TA and FeCl2·4H2O at a certain concentration, and using Fe2+ Oxidized to Fe 3+ It also dynamically coordinates with TA to control the growth of the rough middle layer on the sponge skeleton in time and space, thereby regulating the TA-Fe 3+ Thickness and roughness of the deposited layers of the network.
[0010] Furthermore, the preparation method specifically comprises the following steps:
[0011] Step 1: Dissolve tannic acid TA and FeCl2·4H2O in deionized water to prepare solutions with concentrations of 2.0-8.0 mg / mL and 2.4-9.6 mg / mL, respectively;
[0012] Step 2: The TA solution prepared in step 1 and the FeCl2·4H2O solution were quickly mixed and stirred evenly in a volume ratio of 1:1, and then the commercial sponge was immediately and completely immersed in the mixed solution;
[0013] It should be noted that types of commercial sponges include melamine sponge, polyurethane sponge, polyester sponge and polyethylene sponge.
[0014] Step 3: As time goes by, the Fe content in the mixed solution increases. 2+ Gradually converted to Fe 3+ The formed spherical metal-phenol nanoparticles are deposited on the sponge skeleton over time, the color of the mixed solution gradually deepens, and the thickness of the coating on the surface of the sponge skeleton increases. After reacting for 2-6 hours, the sponge is taken out and the surface residues are repeatedly washed with deionized water;
[0015] Step 4: dissolve octadecylamine in anhydrous ethanol to prepare a solution with a concentration of 5-20 mg / mL, place the sponge obtained in step 3 in the solution, wait for the reaction for 0.5-2 hours, take it out, wash it repeatedly with anhydrous ethanol and deionized water for 3-5 times, and dry it in an oven at 40-80°C to obtain a super hydrophobic / super oleophilic sponge with a lotus leaf-like rough spherical structure and low surface energy molecular modification, that is, the super hydrophobic sponge with a hierarchical rough surface mediated by the metal-phenolic network.
[0016] It should be noted that the two factors that affect hydrophilicity and hydrophobicity are the roughness structure and the properties of the surface molecules. For molecules with fixed surface energy, such as octadecylamine, the greater the surface roughness, the stronger its hydrophobicity. In addition, such hydrophobic molecules cannot be directly modified on the sponge surface and require an intermediate layer for reaction connection. Therefore, TA-Fe 3+ The role of is to construct a rough morphology on the one hand, and to fix the low surface energy molecule octadecylamine on the other hand.
[0017] The third technical purpose of the present invention is to provide a super-hydrophobic sponge with a hierarchical rough surface mediated by a metal-phenolic network as described above for use in the separation of oily wastewater.
[0018] Specifically, the composite sponge prepared by the present invention has super hydrophobic / super oleophilic properties, and maintains stable wettability in strong acid, strong alkali, and high salt environments, and can be used in fields such as handling offshore oil spill accidents or industrial oily wastewater discharge.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The present invention utilizes Fe 2+ The oxidation of tannic acid TA undergoes a coordination reaction, and its non-selective properties are used to adhere to the sponge skeleton to construct a hierarchical spherical micro-nano structure, avoiding the complex post-modification process of traditional coating technology.
[0021] 2. The present invention controls the rough morphology and deposition thickness of the micro-nano structure by adjusting the concentrations of tannic acid TA and FeCl2·4H2O and the oxidation time, which is helpful for the subsequent regulation of the wettability of the sponge.
[0022] 3. The present invention utilizes TA-Fe modified on the surface of the sponge skeleton 3+ The chemical reaction between the intermediate layer and the low surface energy molecule octadecylamine produces a composite sponge with superhydrophobicity / superoleophilicity, a contact angle greater than 165°, and can be used to efficiently separate oily wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0024] Figure 1 It is a TA-Fe constructed with different strategies 3+ Coating morphology: (a) direct assembly; (b) layer-by-layer self-assembly; (c) oxidative self-assembly.
[0025] Figure 2 are the contact angles of hydrophobic sponges constructed by different strategies: MS@D-OA, MS@LBL-OA and MS@OMC-OA represent the water contact angles of composite sponges constructed by direct assembly, layer-by-layer self-assembly and oxidative self-assembly strategies, respectively.
[0026] Figure 3 The microscopic morphology images of the sponge: (a) microscopic images of the original sponge at different magnifications; (b) TA, Fe 2+Microscopic images of the modified sponge at different magnifications; (c) Microscopic image of the sponge modified with octadecylamine; (d) EDX image of the sponge modified with octadecylamine.
[0027] Figure 4 The hydrophobic / oleophilic properties of the composite sponge: (a) wettability of the surface and interior of the composite sponge; (b) resistance of the composite sponge to different aqueous liquids; (c) hydrophobic images of the sponge before and after modification; (d) superhydrophobic properties of the sponge under oil; (e) characterization of the dynamic adhesion performance of the composite sponge to water droplets.
[0028] Figure 5 The hydrophobic properties of the composite sponge in different acid-base environments (a) and extreme environments (b).
[0029] Figure 6 The adsorption performance of the composite sponge for different types of oil (a) and the adsorption performance for hexane after 30 cycles (b). DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.
[0032] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.
[0033] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.
[0034] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.
[0035] The invention discloses a metal-phenolic network-mediated super-hydrophobic sponge with a layered rough surface and a preparation method thereof.
[0036] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.
[0037] Embodiment 1:
[0038] Step 1: Dissolve TA and FeCl2·4H2O in deionized water to prepare solutions with TA concentration of 4.0 mg / mL and FeCl2·4H2O concentration of 4.8 mg / mL respectively.
[0039] Step 2: Take 500 mL of the freshly prepared TA solution in step 1 and 500 mL of the FeCl2·4H2O solution, mix them quickly and stir them evenly, and then immediately immerse a commercial sponge with a volume of 20 cm×20 cm×2 cm completely in the mixed solution.
[0040] Step 3: After 6 hours of reaction, part of the Fe in the mixture 2+ Gradually converted to Fe 3+ , the sponge changes from its original color to dark purple. Take out the sponge and use deionized water to repeatedly clean the surface residues before setting aside.
[0041] Step 4: Dissolve octadecylamine in anhydrous ethanol to prepare a solution with a concentration of 10 mg / mL, then immerse the sponge obtained in step 3, react for 0.5 h, take it out, and repeatedly wash it with anhydrous ethanol and deionized water for 3-5 times. After drying, a superhydrophobic / superoleophilic sponge that can be used for separation of oil-water mixtures is obtained.
[0042] The surface of the obtained bionic superhydrophobic sponge is purple-red, and the scanning electron microscope image shows that its surface morphology is layered spherical, with large roughness, a water contact angle greater than 160°, and it remains stable in the adsorption of oil products during 30 cycle tests.
[0043] Embodiment 2:
[0044] Step 1: Dissolve TA and FeCl2·4H2O in deionized water to prepare solutions with TA concentration of 2.0 mg / mL and FeCl2·4H2O concentration of 2.4 mg / mL respectively.
[0045] Step 2: Take 500 mL of the freshly prepared TA solution in step 1 and 500 mL of the FeCl2·4H2O solution, mix them quickly and stir them evenly, and then immediately immerse a commercial sponge with a volume of 20 cm×20 cm×2 cm completely in the mixed solution.
[0046] Step 3: After 3 hours of reaction, part of the Fe 2+ Gradually converted to Fe 3+ , the sponge changes from its original color to lavender. Take out the sponge and use deionized water to repeatedly clean the surface residues before setting aside.
[0047] Step 4: Dissolve octadecylamine in anhydrous ethanol to prepare a solution with a concentration of 5 mg / mL, then immerse the sponge obtained in step 3 in it, react for 0.5 h, take it out, and repeatedly wash it with anhydrous ethanol and deionized water for 3-5 times. After drying, a superhydrophobic / superoleophilic sponge that can be used for separation of oil-water mixtures is obtained.
[0048] The surface of the obtained bionic superhydrophobic sponge is pink. The scanning electron microscope image shows that its surface morphology is layered spherical with obvious rough spherical structure. The water contact angle is greater than 150°, and the adsorption of oil remains stable in 30 cycle tests.
[0049] Embodiment 3:
[0050] Step 1: Dissolve TA and FeCl2·4H2O in deionized water to prepare solutions with TA concentration of 4.0 mg / mL and FeCl2·4H2O concentration of 4.8 mg / mL respectively.
[0051] Step 2: Take 500 mL of the freshly prepared TA solution in step 1 and 500 mL of the FeCl2·4H2O solution, mix them quickly and stir them evenly, and then immediately immerse a commercial sponge with a volume of 20 cm×20 cm×2 cm completely in the mixed solution.
[0052] Step 3: After 2 hours of reaction, part of the Fe in the mixture 2+ Gradually converted to Fe 3+ , the sponge changes from its original color to dark purple. Take out the sponge and use deionized water to repeatedly clean the surface residues before setting aside.
[0053] Step 4: Dissolve octadecylamine in anhydrous ethanol to prepare a solution with a concentration of 5 mg / mL, then immerse the sponge obtained in step 3 in it, react for 0.5 h, take it out, and repeatedly wash it with anhydrous ethanol and deionized water for 3-5 times. After drying, a superhydrophobic / superoleophilic sponge that can be used for separation of oil-water mixtures is obtained.
[0054] The surface of the obtained bionic superhydrophobic sponge is pink, and the scanning electron microscope image shows that its surface morphology is layered spherical, with large roughness, a water contact angle greater than 155°, and it remains stable in the adsorption of oil products during 30 cycle tests.
[0055] In order to further demonstrate the beneficial effects of the present invention and to better understand the present invention, the following characterization experiments and application tests are conducted to further illustrate the technical features disclosed in the present invention, but they should not be construed as limitations on the present invention. Other improvements made by those skilled in the art based on the above invention content without inventive work are also considered to fall within the scope of protection of the present invention. Characterization and application experiments:
[0056] A method for preparing a biomimetic superhydrophobic oil-water separation sponge mediated by a metal-phenolic network, which achieves the construction of a hierarchical rough intermediate layer by adjusting the coordination strategy of the metal-phenolic network without introducing additional micro-nanoparticles, and then obtains a sponge with superhydrophobic properties by modifying it with octadecylamine hydrophobic chains.
[0057] Use Fe 3+ The coordination reaction with TA builds the middle layer, and through TA-Fe 3+ The reaction of Fe networks with other substances to prepare surfaces with specific functions has been studied and applied, but the conventional use of Fe 3+ The surface of the sponge modified by direct assembly or layer-by-layer self-assembly of TA is relatively flat ( Figure 1 ), the subsequent sponge is difficult to achieve super hydrophobic effect ( Figure 2 ). Therefore, the present invention utilizes Fe 2+ Instead of Fe 3+ , through Fe 2+ Slowly oxidized to Fe 3+ The TA undergoes a coordination reaction to generate spherical metal-phenol particles in situ on the sponge surface to construct a rough layered biomimetic surface. After modification with octadecylamine, the composite sponge exhibits excellent hydrophobicity, with a water contact angle greater than 165°, and has hydrophobic stability in application environments such as strong acid, strong base and high salt ( Figure 4 and Figure 5 ).
[0058] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A metal-phenolic network-mediated superhydrophobic sponge with a hierarchical rough surface, characterized in that: Using TA-Fe tannate 3+ The phenolic hydroxyl groups of tannic acid (TA) molecules in the network reacted with the amino groups in octadecylamine molecules through Michael addition reaction and Schiff base reaction, and the low surface energy molecule octadecylamine was modified on the sponge skeleton to prepare a biomimetic superhydrophobic sponge with a rough hierarchical structure and low surface energy.
2. A method for preparing a metal-phenolic network-mediated superhydrophobic sponge with a hierarchical rough surface as claimed in claim 1, characterized in that: The porous sponge was immersed in a mixture of tannic acid TA and FeCl2·4H2O with a certain concentration. 2+ Oxidized to Fe 3+ It also dynamically coordinates with TA to control the growth of the rough middle layer on the sponge skeleton in time and space, thereby regulating the TA-Fe 3+ Thickness and roughness of the deposited layers of the network.
3. The method for preparing a metal-phenolic network-mediated superhydrophobic sponge having a hierarchical rough surface according to claim 2, characterized in that: The method specifically comprises the following steps: Step 1: Dissolve tannic acid TA and FeCl2·4H2O in deionized water to prepare tannic acid TA solution and FeCl2·4H2O solution respectively; Step 2: The tannic acid TA solution and the FeCl2·4H2O solution prepared in step 1 are quickly mixed and stirred evenly, and then the commercial sponge is immediately immersed in the mixed solution to react. After a period of time, the sponge is taken out and the surface residue is repeatedly washed with deionized water for later use; Step 3: dissolving octadecylamine in anhydrous ethanol to prepare an octadecylamine solution, placing the sponge obtained in step 2 in the solution for reaction, then taking out the solution and repeatedly washing it with anhydrous ethanol and deionized water, and drying the solution to obtain a superhydrophobic / superoleophilic sponge having a lotus leaf-like rough spherical structure and low surface energy molecular modification, i.e., the superhydrophobic sponge having a hierarchical rough surface mediated by the metal-phenolic network.
4. The method for preparing a metal-phenolic network-mediated superhydrophobic sponge having a hierarchical rough surface according to claim 3, characterized in that: The concentration of tannic acid TA solution is 2.0-8.0 mg / mL, and the concentration of FeCl2·4H2O solution is 2.4-9.6 mg / mL.
5. The method for preparing a metal-phenolic network-mediated superhydrophobic sponge having a hierarchical rough surface according to claim 3, characterized in that: In step 2, the mixing volume ratio of tannic acid TA solution and FeCl2·4H2O solution is 1:1, and the reaction time after the commercial sponge is immersed is 2-6h.
6. The method for preparing a metal-phenolic network-mediated superhydrophobic sponge having a hierarchical rough surface according to claim 3, characterized in that: In step 3, the concentration of the octadecylamine solution is 5-20 mg / mL, the reaction time is 0.5-2 h, and the drying temperature is 40-80° C.
7. Use of the metal-phenolic network-mediated superhydrophobic sponge with a hierarchical rough surface as claimed in claim 1 or the metal-phenolic network-mediated superhydrophobic sponge with a hierarchical rough surface prepared by the method as claimed in claim 2 or 3 in the separation of oily wastewater.